The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1250/ast.24.7
|View full text |Cite
|
Sign up to set email alerts
|

A pitch detection method based on continuous wavelet transform for harmonic signal

Abstract: In order to track a rapid transient of pitch, a required frame length of some conventional pitch detection methods is too long. Although there are wavelet based pitch detection methods which require only a few periods of pitch for a frame, they are not robust enough against noise. This paper proposes a new pitch detection method which can work properly under noisy environments even if a frame duration is short. The proposed method consists of a power level detector, a signal analyzer, an autocorrelator, a voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…According to the result, doubled pitch is estimated in some durations where a fundamental frequency is less than 90 Hz. The result has almost the same characteristics as that of simulation shown in the previous study [1]. Furthermore, result of pitch detection for speech is shown in Fig.…”
Section: Real-time Pitch Detection Using the Clustersupporting
confidence: 77%
See 3 more Smart Citations
“…According to the result, doubled pitch is estimated in some durations where a fundamental frequency is less than 90 Hz. The result has almost the same characteristics as that of simulation shown in the previous study [1]. Furthermore, result of pitch detection for speech is shown in Fig.…”
Section: Real-time Pitch Detection Using the Clustersupporting
confidence: 77%
“…The previous study with respect to the pitch detection method, called the harmonic wavelet transform method [1] showed that it takes a longer processing time because the method uses continuous wavelet transform which requires heavy calculation cost due to many convolutions. The harmonic wavelet transform method consists of 5 blocks; a power level detector, a signal analyzer, an autocorrelator, a voiced-unvoiced detector and a lag time interpolator.…”
Section: Parallel Pitch Detection Algorithm Based On Harmonic Waveletmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a wide variety of algorithms for pitch detection have been proposed in the speech processing literature, such as the autocorrelation, cepstrum-based methods LPC method and Average magnitude difference function and so on [6]. Since the glottal closure is marked by a sharp discontinuity in the speech signal, it can in some sense be related to the edge detection problem in image processing.…”
Section: A Pitch Detectionmentioning
confidence: 99%